From a German perspective: Works council 4.0 - digital and global? - Thomas Klebe (Hugo Sinzheimer Institut für Arbeitsrecht (HSI), 2018)
Companies as well as the world of work are both currently undergoing a massive transformation. In addition to digitalisation, globalisation of enterprises and flexibilisation of their organisational forms the socio-political conditions are also changing with significant consequences for the firm and for work within the firm. Without going into details it has to be stressed that there is a change of values referring to the society as a whole and in particular to family arrangements as well as time distribution between work and private life. Work life balance plays an ever increasing role. The digitalization in everybody's daily life ('always on'), the demographic development, environmental problems such as energy policy or the electrification of drive-trains in the automobile industry, the migration issue and people's increasing desire for participation, in particular for employee involvement in management's decision-making are key factors of the indicated transformation. All these social developments also affect the activities of works councils and trade unions, of codetermination and the shaping of working life in enterprises. The following considerations, however, merely will focus on current company strategies and their effects on the works council's role.
Keywords: 340